Flat-Gain L-Band EDFA with Two-Stage Double Pass Configuration - S.W, Harun; N, Tamchek; T, Subramaniam; H, Ahmad (Malaysian Journal of Science (MJS), 2003)
An experiment on highly efficient flat-gain long wavelength band erbium doped fiber amplifier (L-band EDFA) is demonstrated using two-stage double-pass configuration. It uses a circulator at the end of the two-stage amplifier to allow double propagation of signal in the erbium-doped fibers (EDFs). The two-stage double-pass amplifier has achieved a flat-gain output at 33.5dB, which is 13.5dB higher than that of the single pass system with only 84mW pumping of a 980nm laser diode. The gain variation was within 1dB over 30nm from the wavelength of 1570 to l600nm. The noise figure at flat gain region varies from 6.9 to 11.5dB. The flat-gain spectrum can be maintained even with the existing of 32 channels at Ã¢â‚¬â€30dBm in the system.